2015
DOI: 10.1088/0264-9381/32/24/243001
|View full text |Cite
|
Sign up to set email alerts
|

Testing general relativity with present and future astrophysical observations

Abstract: One century after its formulation, Einsteinʼs general relativity (GR) has made remarkable predictions and turned out to be compatible with all experimental tests. Most of these tests probe the theory in the weak-field regime, and there are theoretical and experimental reasons to believe that GR should be modified when Class. Quantum Grav. 32 (2015) 243001Topical Review physical laboratories to probe strong-field gravity are black holes and neutron stars, whether isolated or in binary systems. We review the mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
1,359
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,324 publications
(1,391 citation statements)
references
References 884 publications
(1,815 reference statements)
11
1,359
0
3
Order By: Relevance
“…Many summaries of existing and prospective tests of gravity were written prior to the gravitational wave event; some recent examples that we recommend are [61,62,63,59] . There has also been detailed analysis of the implications of GW150914 itself for gravitational physics [64,65].…”
Section: Implications For Gravitational Physicsmentioning
confidence: 99%
“…Many summaries of existing and prospective tests of gravity were written prior to the gravitational wave event; some recent examples that we recommend are [61,62,63,59] . There has also been detailed analysis of the implications of GW150914 itself for gravitational physics [64,65].…”
Section: Implications For Gravitational Physicsmentioning
confidence: 99%
“…The screening can be accomplished in many ways [19,60]: with a weak coupling between the field and matter in regions of high density, thus inducing a weak fifth-force as in symmetron theories [52,53]; the field can acquire a large mass in high density environments, being short-ranged and undetectable, and be light and long-ranged in lower density regions, as for chameleon fields [20,61,62,75,76] and f (R) models [27,28,36,96]; or one may change the kinetic contribution of the field to the Lagrangian, with first or second order derivatives becoming important in a certain range, as it happens with the Vainshtein screening mechanism [101].…”
Section: Introductionmentioning
confidence: 99%
“…For more details on the implementation of the scalar fields and other technicalities we refer to . For this purpose, we focus on simple observables such as the matter power spectrum, halo mass function, density profiles, and velocity profiles to investigate modified gravity signatures that were previously studied in Li et al (2012bLi et al ( , 2013, Hammami et al (2015), Schmidt et al (2009), Gronke et al (2015, Lombriser et al (2012Lombriser et al ( , 2014, Winther et al (2012), Terukina & Yamamoto (2012), Shi et al (2015), Pujol et al (2014), Hellwing et al (2013), He et al (2013He et al ( , 2015, Schmidt (2010), Brax et al (2013), Tessore et al (2015), Gronke et al (2015) that can also be observed (Berti et al 2015;Zivick et al 2015;Mak et al 2012;Cai et al 2015;Song et al 2015;Wilcox et al 2015;Jain & Khoury 2010;Schmidt 2010;Hellwing et al 2014). This paper is organized as follows: in Sect.…”
Section: Introductionmentioning
confidence: 99%